Outcomes of patients after successful left ventricular assist device explantation: a EUROMACS study. (20th March 2020) - Antonides, Christiaan F.J.; Schoenrath, Felix; de By, Theo M.M.H.; Muslem, Rahatullah; Veen, Kevin; Yalcin, Yunus C.; Netuka, Ivan; Gummert, Jan; Potapov, Evgenij V.; Meyns, Bart; Özbaran, Mustafa; Schibilsky, David; et al.
Abstract: Aims: Sufficient myocardial recovery with the subsequent explantation of a left ventricular assist device (LVAD) occurs in approximately 1–2% of the cases. However, follow‐up data about this condition are scarcely available in the literature. This study aimed to report the long‐term outcomes and clinical management following LVAD explantation. Methods and results: An analysis of the European Registry for Patients with Mechanical Circulatory Support was performed to identify all adult patients with myocardial recovery and successful explantation. Pre‐implant characteristics were retrieved and compared with the non‐recovery patients. The follow‐up data after explantation were collected via a questionnaire. A Kaplan–Meier analysis for freedom of the composite endpoint of death, heart transplantation, LVAD reimplantion, or heart failure (HF) relapse was conducted. A total of 45 (1.4%) cases with myocardial recovery resulting in successful LVAD explantation were identified. Compared with those who did not experience myocardial recovery, the explanted patients were younger (44 vs. 56 years, P < 0.001), had a shorter duration of cardiac disease ( P < 0.001), and were less likely to have ischaemic cardiomyopathy (9% vs. 41.8%, P < 0.001). Follow‐up after explantation could be acquired in 28 (62%) cases. The median age at LVAD implantation was 43 years (inter‐quartile range: 29–52), and 23 (82%) were male. Baseline left ventricular ejection fraction was 18% (inter‐quartile range: 10–20%), and 60.7% of the patients had Interagency Registry for Mechanically Assisted Circulatory Support Profile 1 or 2. Aetiologies of HF were dilated cardiomyopathy in 36%, myocarditis in 32%, and ischaemic in 14% of the patients, and 18% had miscellaneous aetiologies. The devices implanted were HeartMate II in 14 (50%), HVAD in 11 (39%), HeartMate 3 in 2 (7%), and 1 unknown with a median duration of support of 410 days (range: 59–1286). The median follow‐up after explantation was 26 months (range 0.3–73 months), and 82% of the patients were in New York Heart Association Class I or II. Beta‐blockers were prescribed to 85%, angiotensin‐converting enzyme inhibitors to 71%, and loop diuretics to 50% of the patients, respectively. Freedom from the composite endpoint was 100% after 30 days and 88% after 2 years. Conclusions: The survival after LVAD explantation is excellent without the need for heart transplantation or LVAD reimplantation. Only a minority of the patients suffer from a relapse of significant HF.